The influence of access to technology and digital literacy on female empowerment and digital entrepreneurial intentions - Ali Saleh Alshebami; Syed Ali Fazal; Abdullah M. Aljarodi; Nowshin Zarin; Abdullah Hamoud Ali Seraj; Elham Alzain (Problems and Perspectives in Management)
Women’s empowerment is crucial for achieving Sustainable Development Goal 5, which seeks to eliminate all discrimination against women and promote effective female participation and equal opportunities. Education is one of the most powerful tools for empowering women. Therefore, this paper aims to examine the relationship between access to technology, digital literacy, digital entrepreneurial intent, and female empowerment, using data from 217 female university students in Saudi Arabia. Conformity factor analysis (CFA) and multivariate covariance-based structural equation modelling (CB-SEM) were utilised to explore this complex relationship. The path analysis reveals a significant link between access to technology and female empowerment. Technology can substantially influence individuals’ lives by enabling women to make informed decisions and shape their futures, thus promoting gender equality. For young students especially, access to and use of technology can positively support their social inclusion and independence. An important positive effect of digital literacy on both digital entrepreneurial intent and female empowerment is also observed. The ability to effectively use communication and information technology depends on access to and proficiency with such technology. Additionally, individuals’ motivation to seek information and their plans to attain business objectives using the Internet rely on their digital literacy. Finally, the results confirm a significant mediating role of digital literacy in the influence of access to technology on digital entrepreneurial intent and female empowerment, suggesting that individuals can only benefit from access to technology if they have the ability to utilise communication and information technology.